Genital Piercing: Childhood and Adolescent Behaviors That Serve as Predictors and Scores on Scales Measuring Hypersexuality and Risky Sexual Behavior, Sexual Orientation, Depression, Conflict, Intimacy, and Sexual Satisfaction. Issue 1 (3rd April 2017) - Griffee, Karen; Beard, Keith W.; Stroebel, Sandra S.; Harper-Dorton, Karen V.; O'Keefe, Stephen L.; Young, Debra H.; Swindell, Sam; Stroupe, Walter E.; Steele, Kerri; Lawhon, Megan; Kuo, Shih-Ya
ABSTRACT: Groups of 62 women and 25 men with genital piercings were compared to same-sex controls without genital piercing (2, 549 women and 1, 427 men, respectively) on measures of sexual orientation, intimacy, conflict, sexual satisfaction, depression, numbers of sexual partners, and numbers of times they engaged in sexual behaviors with female and male partners as adults. As adults, both women and men with genital piercings scored higher on the measures of same-sex orientation, hypersexuality, and risky sexual behavior and had more adult male partners and same-sex partners than controls. Women with genital piercings were more likely than controls to endorse being sexually addicted.